DANCER: Study protocol of a prospective, non-randomized controlled trial for crossed limb versus standard limb configuration in endovascular abdominal aortic aneurysm repair - Shen, Yinzhi; Wang, Jiarong; Zhao, Jichun; Yuan, Ding; Wang, Tiehao; Huang, Bin (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background Hostile anatomy, especially severely angulated neck and tortuous iliac arteries, has always been a conundrum in endovascular aneurysm repair (EVAR). Crossed limb (CL) graft, also called the “ballerina technique”, has been utilized to address this problem by facilitating gate cannulation. In terms of short and long-term outcomes, correlated studies have made inconsistent conclusions and this issue remains controversial. Based on a previous cohort study conducted in our center, we aim to prospectively compare the safety and efficacy between CL and standard limb (SL) configuration in patients receiving EVAR. Methods This is a prospective, single-center, non-randomized controlled trial. A total of 275 patients who meet the inclusion criteria will be enrolled and allocated with a 4:11 ratio of CL to SL, which is based on results of our previous study. All patients will receive same perioperative management and postoperative medications. All EVAR procedures will be performed under standard protocol, utilizing Endurant II or IIs Stent Graft. The configuration of the graft stent will be decided by surgeons and confirmed by final angiography. The primary outcome is 3-year freedom from major adverse limb-graft events (MALEs). Endpoints will be assessed at the following time points: 1, 6, 12, 24 and 36 months. Discussion: To our best knowledge, this crosseD versus stANdard Configuration in Endovascular Repair (DANCER) trial is the first non-randomized controlled trial to compare these two graft configurations in EVAR. The main aim is to compare the MALEs between two groups at 3 years postoperatively. This trial will hopefully provide high-level evidence for employing CL in EVAR. Clinical Trial registration This trial has been prospectively registered in Chinese Clinical Trial Registry on 10th Nov 2021. Registration number: ChiCTR2100053055. Keywords: Non-randomized controlled trial; Crossed limb; Standard limb; EVAR; Abdominal aortic aneurysm